Description of a new species of Pareiorhina (Siluriformes: Loricariidae) from the rio São Francisco basin, Brazil - Silva, Gabriel S. C.; Roxo, Fábio F.; Oyakawa, Osvaldo T. (Zootaxa, 2016)
In the present paper we describe a new species of Pareiorhina from Minas Gerais State, Brazil. The new species is distinguished from its congeners by a combination of the following characters: the dorsal surface of caudal peduncle strongly concave, 30 vertebrae, bicuspid teeth, a conspicuous cylindrical shaped papilla between the oral valve and premaxilla, smaller odontodes along the snout margin, a small orbital diameter, a higher head width, a shorter interorbital width, a shorter predorsal length, a shorter cleithral width, and a shorter caudal peduncle depth. The new species is known from four small streams of the rio São Francisco basin: one tributary of the rio Maranhão, one tributary of the rio Paraopeba and two tributaries of the Rio das Velhas. This species is found in fast-flowing streams associated with rocks and sand in the bottom of the rivers.